Optical Properties of Carbon Dots in the Deep‐Red to Near‐Infrared Region Are Attractive for Biomedical Applications. Issue 43 (8th August 2021) - Li, Di; Ushakova, Elena V.; Rogach, Andrey L.; Qu, Songnan
Abstract: Carbon dots (CDs) represent a recently emerged class of luminescent materials with a great potential for biomedical theranostics, and there are a lot of efforts to shift their absorption and emission toward deep‐red (DR) to near‐infrared (NIR) region falling in the biological transparency window. This review offers comprehensive insights into the synthesis strategies aimed to achieve this goal, and the current approaches of modulating the optical properties of CDs over the DR to NIR region. The underlying mechanisms of their absorption, photoluminescence, and chemiluminescence, as well as the related photophysical processes of photothermal conversion and formation of reactive oxygen species are considered. The already available biomedical applications of CDs, such as in the photoacoustic imaging and photothermal therapy, photodynamic therapy, and their use as bioimaging agents and drug carriers are then shortly summarized. Abstract : Carbon dots (CDs) with optical transitions in deep‐red to near‐infrared spectral range have experienced a rapid development within recent years. This review provides comprehensive insights into the current approaches of modulating the optical properties of such CDs, emphasizes the underlying mechanisms and related photophysical processes, and shortly summarizes their related biomedical applications.